Queen's Royal College, Trinidad, B.W.I. - (:unkn) unknown (Muir, Marshall and Co., Trinidad, 2010)
Exterior view of the Queen’s Royal College situated at the corner of St. Clair Avenue and Maraval Road in Port of Spain, Trinidad. This is a secondary school that admits male students only. In the foreground is the Queen's Park Savannah and the tree to the left is a Samaan Tree. A tramcar with passengers is passing by. Postcard number i15464.
Colour: Black and White; Style: Landscape; Other: Bordered, Divided.
Keywords: Trinidad and Tobago; Postcards; [1930]; Urban transportation--Trinidad and Tobago; Schools--Trinidad and Tobago; Street-railroads--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Historic buildings--Trinidad and Tobago; High schools--Trinidad and Tobago; Public schools--Trinidad and Tobago; Education, Secondary--Trinidad and Tobago; Architecture--Trinidad and Tobago; Architecture--Details; Towers--Trinidad and Tobago; Palms--Trinidad and Tobago; Windows--Trinidad and Tobago; Clocks and watches--Trinidad and Tobago; Tower clocks--Trinidad and Tobago; Trees--Trinidad and Tobago; Magnificent Seven, The (Port of Spain); Queen's Park Savannah (Port of Spain); Queen's Royal College (Trinidad and Tobago)